THE EFFECT OF PERSONAL AND SITUATIONAL FACTORS ON THE INTENTION OF WHISTLEBLOWING WITH MODERATED LEGAL PROTECTION - Rahman, Daisar; Hayati, Nur (UI Scholars Hub, 2021)
This research is to determine the effectiveness of legal protection in strengthening the relationship between attitude toward behavior, subjective norm, perceived behavioral control, the seriousness of wrongdoing, status of the wrongdoer, and reward with whistleblowing intentions. The population in this research was civil servants who were Regional Inspectors in all regencies in Madura. The sampling technique in this study was purposive sampling consisting of 104 civil servants who had functional positions as auditors, staffing auditors, or supervisors of regional government (P2UPD). Data was collected by distributing questionnaires directly to the respondents. The data analysis technique used in this study was PLS-SEM by using Smart-PLS 3.0 software. The results of the study found that (1) Attitude toward behavior, subjective norm, and reward affect whistleblowing intentions; (2) Perceived behavioral control, seriousness of wrongdoing, and status of the wrongdoer does not affect whistleblowing intentions; (3) Legal protection is unable to strengthen the relationship between attitude toward behavior, subjective norm, perceived behavioral control, the seriousness of wrongdoing, status of the wrongdoer, and reward with whistleblowing intentions.